CASH WAQF LINK SUKUK EDUCATION PROGRAM (CWLS) PROPINSI RIAU - Waldelmi, Idel; Aquino, Afvan; Listihana, Wita Dwika; Widya, Rahma; Tinambunan, Kevin Delfitho (Komunitas Manajemen Kompetitif, 2025)
The Cash Waqf Linked Sukuk (CWLS) Education National Webinar was held on January 7, 2025 with guest speaker Dr. Syauki Beik. This activity aims to increase public literacy on CWLS instruments as an innovative and sharia-based cash waqf management. The webinar was attended by waqf practitioners, Islamic financial institutions, academics, students, and the general public. Based on the survey results, this education succeeded in significantly increasing the participants' knowledge, understanding, and confidence in CWLS. Before the education, the level of public literacy towards CWLS tended to be low, but afterward there was a notable increase in the aspects of understanding and belief in the benefits of CWLS. The resulting suggestions include the need for continuous education, strengthening the transparency of waqf fund management, developing innovative CWLS products, and optimizing digital access. With the collaboration of all parties, CWLS is expected to be a strategic instrument in empowering the ummah's economy and supporting sustainable national development according to sharia principles KEYWORDS CWLS; Waqf Education; Islamic finance; Sharia Compliance